Editorial: time to treat the climate and nature crisis as one indivisible global health emergency - Kamran ABBASI; Parveen ALI; Virginia BARBOUR; Thomas BENFIELD; Kirsten BIBBINSDOMINGO; Stephen HANCOCKS; Richard HORTON; Laurie LAYBOURN-LANGTON; Robert MASH; Peush SAHNI; Wadeia MOHAMMAD SHARIEF; Paul YONGA; et al. (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2023)
Over 200 health journals call on the United Nations, political leaders, and health professionals to recognise that climate change and biodiversity loss are one indivisible crisis and must be tackled together to preserve health and avoid catastrophe. This overall environmental crisis is now so severe as to be a global health emergency. The world is currently responding to the climate crisis and the nature crisis as if they were separate challenges. This is a dangerous mistake. The 28th Conference of the Parties (COP) on climate change is about to be held in Dubai while the 16th COP on biodiversity is due to be held in Turkey in 2024. The research communities that provide the evidence for the two COPs are unfortunately largely separate, but they were brought together for a workshop in 2020 when they concluded that: "Only by considering climate and biodiversity as parts of the same complex problem…can solutions be developed that avoid maladaptation and maximize the beneficial outcomes